A new fiddler crab species (Brachyura: Ocypodidae) from the Pacific coast of Panama - Lombardo, Roberto (Revista Ciencias Marinas y Costeras, 2026)
A new fiddler crab species of the genus Leptuca, discovered at five sites along the Panamanian Pacific coast, is described here. Specimens were collected from mangrove edges during diurnal low tides between June 2024 and August 2025. Morphological traits were consistent across all sites, with an average carapace width of 12.53 ± 1.81 mm. Diagnostic features include bacilliform, V-shaped patches of pubescence on the mesogastric region; a squared manus carpal cavity with a distinct distal beaded edge; a robust oblique ridge elevated into a triangular projection; a dactyl ventral margin with a large, rounded tooth; and paired beaded ridges on the posterior surface of the second or third ambulatory carpi. The proposed species name is Leptuca bacillopilosa sp. nov., in reference to the characteristic symmetrical rod‐like pile patches on the carapace. This discovery enhances the understanding of fiddler crab diversity in the region and highlights the significance of continued taxonomic surveys.